Comparative Evaluation of the Allelopathic Effects of the Leaf Extracts of Three Asteraceae Species (Ageratum conyzoides, Vernonia amygdalina, Artemisia annua) - Chamberlain Solomon Bassey; Emmanuel Paul Okoi (Archives of Current Research International, 2018)
Search for an alternative to chemical herbicides have prompted researchers to investigate the allelopathic potential of plants, which would serve as a remedy for contamination of soil, water bodies and crops products with toxic chemical residues derived from using synthetic herbicides. The allelopathic effects of the aqueous leaf extracts of Ageratum conyzoides, Vernonia amygdalina and Artemisia annua at 0.05, 0.1, 0.2 and 0.5 (part per volume) concentrations were evaluated on seed germination, root length and height of seedlings of Lactuca sativa after 28 days in vitro. Results obtained showed significant differences P=[0.5] among the different concentrations of aqueous leaf extracts used when compared with the control in all the three parameters studied. Significant reduction in seed germination, growth of root and height of seedlings were observed in all the treatments but at varying levels from moderate to severe effects for aqueous leaf extract of A. conyzoides and A. annua respectively, while on the contrary, aqueous extracts of V. amygdalina enhanced seed germination, root elongation and plant height. Cytological studies conducted to observe the mitotic behaviour of cells in root tips obtained from highest concentration of the leaf extracts indicated that aqueous leaf extracts of A. conyzoides and A. annua lowered the mitotic index of cells in root tips of Lactuca sativa while that of V. amygdalina greatly increased the mitotic index of cells in the root tips when compared with the control. For the number of dividing cells, T-test showed significance P=[ 0.001] only in aqueous leaf extract of A. conyzoides.